RISK FACTORS OF CHILHOOD MORTALITY IN URBAN SLUMS OF VARANASI - Mishra, Pankaj; Mishra, R N; Kishore, Surekha; Singh, C M (Indian Journal of Community Health, 2011)
Research Question: What are determinants of Childhood mortality of slums community? Objective: To know Socio-demographic risk factor (determinants) of Childhood mortality of slums community. Material & Methods: Design: Cross Sectional Study; interview technique. Sample Size: 1241 eligible couple from 1411 randomly selected household. Statistical Analysis: Biavariate and Multinomial logistic regression analysis. Result: The risk factors namely per capita income, education of father and mother, occupation of father and mother, frequency of children born, children ever born and surviving males and females child, spacing with which child was born, age at last birth and place of delivery of the last child, the mortality of the index child was significantly high if the child was of first parity.